Extracting software features from online reviews to demonstrate requirements reuse in software engineering - Bakar, Noor Hasrina; Kasirun, Zarinah M.; Salleh, Norsaremah; H. Halim, Azni (Universiti Utara Malaysia (UUM), 2017)
Software Product Lines Engineering is a systematic approach towards realizing software reuse. Among important artifacts to be reused in- cludes requirements, architectures, source codes, designs or even test plans. Requirements reuse if done systematically can expedite the time to market, improve productivity and reduce laborious work. This paper presents the re- sults from an experiment conducted on extracting features from online soft- ware reviews to demonstrate our proposed solution to requirements reuse problem. Fifty two software reviews from seven software categories are used as the test data. The automated process proposed is compared to the manual process and the results from experiment indicates significant im- provements in terms of time efficiency and F-Measure.